(a+b+c)(-a+b+c)(a-b+c)
+(a+b+c)(a-b+c)(a+b-c)
+(a+b+c)(a+b-c)(-a+b+c)
-(-a+b+c)(a-b+c)(a+b-c)
=(a+b+c){(-a+b+c)(a-b+c)
+(a-b+c)(a+b-c)}
+(-a+b+c){(a+b+c)(a+b-c)
-(a-b+c)(a+b-c)}
=(a+b+c){c^2-(a-b)^2+a^2-(b-c)^2}
+(-a+b+c){(a+b)^2-c^2-(a^2-(b-c)^2)}
=a{c^2-(a-b)^2+a^2-(b-c)^2}
-a{(a+b)^2-c^2-(a^2-(b-c)^2)}
+(b+c){c^2-(a-b)^2+a^2-(b-c)^2}
+(b+c){(a+b)^2-c^2-(a^2-(b-c)^2)}
=a{c^2-(a-b)^2+a^2-(b-c)^2
-(a+b)^2+c^2+a^2-(b-c)^2)}
+(b+c){c^2-(a-b)^2+a^2-(b-c)^2
+(a+b)^2-c^2-(a^2-(b-c)^2)}
=a{2c^2-(a-b)^2+2a^2-2(b-c)^2-(a+b)^2}
+(b+c){-(a-b)^2+(a+b)^2}
=a{2c^2-2(a^2+b^2)+2a^2-2(b-c)^2}+(b+c)(4ab)
=2a{c^2-b^2-(b-c)^2}+2a(b+c)(2b)
=2a{c^2-b^2-(b-c)^2+2b(b+c)}
=2a(4bc)
=8abc
お礼
ご回答ありがとうございました。 勉強になりました。